2021
DOI: 10.1016/j.appet.2020.105002
|View full text |Cite
|
Sign up to set email alerts
|

Eating behavior and food purchases during the COVID-19 lockdown: A cross-sectional study among adults in the Netherlands

Abstract: On March 15, 2020, the Dutch Government implemented COVID-19 lockdown measures. Although self-quarantine and social-distancing measures were implemented, restrictions were less severe compared to several other countries. The aim of this study was to assess changes in eating behavior and food purchases among a representative adult sample in the Netherlands (n = 1030), five weeks into lockdown. The results show that most participants did not change their eating behaviors (83.0%) or food purchases (73.3%). Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
246
8
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(301 citation statements)
references
References 41 publications
32
246
8
15
Order By: Relevance
“…Furthermore, in a study conducted in the Netherlands, it was reported that overweight and obese individuals found it more difficult to make healthy food choices. More savory snacks and non-alcoholic beverages were purchased and consumed at home (35.6%) because of more leisure time (31.5%) and boredom (21.9%) during the lockdown (92) .…”
Section: Determinants That Can Influence Body Weight During Pandemicsmentioning
confidence: 99%
“…Furthermore, in a study conducted in the Netherlands, it was reported that overweight and obese individuals found it more difficult to make healthy food choices. More savory snacks and non-alcoholic beverages were purchased and consumed at home (35.6%) because of more leisure time (31.5%) and boredom (21.9%) during the lockdown (92) .…”
Section: Determinants That Can Influence Body Weight During Pandemicsmentioning
confidence: 99%
“…Conversely, in Italy, total PA decreased significantly during the first COVID-19 wave as compared to before, in all age groups and especially in men [ 9 ]. Moreover, several studies have shown small changes in dietary habits [ 10 , 11 , 12 ], while others have reported an increase in unhealthy food intake, overeating, and snacking between meals [ 10 , 13 , 14 , 15 ]. Similarly, studies have indicated that alcohol consumption has not changed during home confinement [ 13 , 16 ], while others have reported increased alcohol consumption [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of the studies have mainly focused on consumers' food consumption behaviors during the lockdown [5,[15][16][17], and many scholars only investigated changes of consumers' traveling behaviors under the pandemic [1,18], but insufficient studies have investigated how people's daily food consumption behavior has been affected after the lockdown or how their behavioral patterns of dining out have been changed under the new normal context. Therefore, in the light of this new context, we intended to examine whether consumers have really adapted to the new normal life, and how their food consumption behaviors have been influenced by factors such as subjective norms, perceived physical and psychological risk, enjoyment, restaurant precautionary measures, and so on.…”
Section: Introductionmentioning
confidence: 99%